PEMBERIAN PROBIOTIK Bacillus sp BERASAL DARI UDANG GALAH (Macrobranchium rosenbergii DE MAN) DAN UDANG WINDU (Penaeus monodon) TERHADAP STATUS KESEHATAN IKAN NILA(Oreochormis niloticus) - Alfian '; Iesje Lukistyowati; Henni Syawal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted on October 2015 - June 2016, at the Laboratory of Microbiology and the Laboratory of Parasites and Fish Diseases, Faculty of Fisheries and Marine Sciences, University of Riau. The purpose of this study is to comprehend the probiotic Bacillus sp. from the digestive tract of the giant prawns (Macrobranchium rosenbergii DE MAN) and the black tiger shrimp (Panaeus monodon) for the health status of tilapia (Oreochormis niloticus). This study uses a Completely Randomized Design (CRD), which consists of three treatments and each of them uses three replications for the probiotic Bacillus sp. treatment of the digestive tract either from the giant prawns or the tiger shrimp. The Bacillus sp. treatment from the giant prawns are P1G (UG4 isolates), P2G isolates combined (UG1, UG2, UG3, UG4, and UG5) and as a control (P0).While the tiger shrimp are using P1W (UWH9 isolates), P2W isolates that combined (UWH1, UWH2, UWH8, UWH9 and UWH 10) and as a control (P0). Probiotics from each treatment were put into the medium water about 3 mL / container with a density of 104 CFU/ml. The results showed that the P1W treatment is the best treatment after infected by Streptococcus iniae for the health statusof tilapia, it is showed by the number of Erythrocytes 246.67x104 sel / mm, Haemoglobin level of 6633 g/dl, Hematocrytes 30.33%, and total Leukocytes 79,33x103 sel/mm3. Given by probiotics of Bacillus sp that originatit from the digestive tract of giant prawns and tiger shrimp through the water were able to maintain the health of tilapia (Oreochormis niloticus).Key Words: Bacillus sp, giant prawns, black tiger shrimp, health status, tilapia